The effect of sexual abuse on self-injurious behaviour among adolescents girls and boys : the mediating factor of self-esteem - Gyða Einarsdóttir 1999- (2021)
The aim of this study was to examine the mediating effect of self-esteem between experience of sexual abuse and the development of self-injurious behaviour, the difference between boys and girls was also examined. Previous studies have shown that sexual abuse is rather frequent in modern society and can have long-term health consequences for both boys and girls. According to studies, childhood sexual abuse has been linked to the development of self-injurious behaviour and low self-esteem in adulthood. The data for this study were collected by Icelandic Centre for Social Research and Analysis “Youth in Iceland 2018” A randomly selected sample of 2,051 adolescents was used in this study. The results showed that self-esteem among the adolescents was lower if they had been sexually abused compared to those who had not been sexually abused. People with lower self-esteem showed a higher incidence of self-injurious behaviour. The findings support previous studies, and it can be concluded that self-esteem can play a role in explaining the connection between sexual abuse and self-injurious behaviour. This information can be used to look for ways to support those who have been victims of sexual abuse and help them reclaim their power. Keywords: Sexual abuse, self-esteem, and self-injurious behaviour Markmið þessarar rannsóknar var að rannsaka miðlunaráhrif sjálfsálits milli reynslu af kynferðis-ofbeldi og þróun sjáfsskaðandi hegðunar, ásamt því að skoða hvort það sé munur milli stráka og stelpna. Fyrri rannsóknir hafa sýnt að kynferðisofbeldi er frekar algengt í nútímasamfélagi og getur haft langvarandi áhrif á heilsu meðal bæði stráka og stelpna. Samkvæmt rannsóknum hefur kynferðisofbeldi í barnæsku verið tengt við þróun á sjálfsskaðandi hegðun og lágt sjálfsálit á fullorðinsárum. Notast var við gögn frá Rannsóknum og greiningu úr spurningarlistanum „Ungt fólk á Íslandi 2018“. Í þessari rannsókn var notað handahófskennt úrtak sem samanstóð af 2,051 unglingum. Niðurstöðurnar sýndu að sjálfsálit meðal unglinga var lægra ...